KAJIAN LITERATUR TENTANG EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Tasya Nabillaiska; Annisa Karima; Tassya Andari; Ari Suriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of the Problem Based Learning (PBL) model in improving elementary school students' learning outcomes through a literature review approach. The persistently low learning outcomes reported in many regions have highlighted the need for a systematic review of innovative learning models, one of which is PBL. The method used is a literature study, analyzing relevant scientific articles published between 2021 and 2024, sourced from Google Scholar, SINTA, and indexed national journals. The findings indicate that the PBL model consistently and significantly improves elementary school students' learning outcomes across various subjects, including Science, Social Studies, Mathematics, and Indonesian Language. These improvements encompass three domains of learning outcomes: cognitive, affective, and psychomotor. Furthermore, PBL has also been shown to foster critical thinking skills, learning motivation, and student independence. However, the effectiveness of PBL is highly dependent on teachers' readiness to design authentic and contextual problem scenarios, as well as adequate learning facilities. This review is expected to serve as a reference for teachers and researchers in implementing and developing the PBL model at the elementary school level.